Abstract Number ‐ 194: Predisposition to Atrial Fibrillation in AIS of Undetermined Source in the Setting of LVO - Omar Choudhury; Alex Chebl; Ali Mohamud; Daniel Miller (Stroke: Vascular and Interventional Neurology, 2023)
Introduction It is estimated that 7.6 million Americans report having had a stroke. Every year, approximately 795,000 people develop a stroke, of which 610,000 are for the first time. Although stroke incidence rates in adults ≥ 65 years of age decreased by 32% per decade from 1987 to 2017, it remains both the fifth leading cause of death and the leading cause of disability in the United States1. Ischemic strokes make up 87% of all strokes and can be categorized by the TOAST classification scheme. Etiologies include large‐vessel atherosclerosis, small vessel disease, cardioembolism, stroke of other determined etiology, and stroke of undetermined etiology2. Cardioembolic strokes, accounting for up to 25% of ischemic strokes typically involve a cardiac insult resulting from either atrial disease, valvular heart disease, structural and functional ventricular diseases, or myocardial infarction. The most common etiology of cardioembolic stroke and focus of this study is atrial fibrillation3. Stroke of undetermined etiology, also called cryptogenic stroke accounts for nearly 30% of ischemic strokes and has been recently coined in the literature as embolic stroke of undetermined source (ESUS) due to the presence of embolic features in the majority of these cases. Atrial cardiomyopathy has been identified as a contributing cause to ESUS with the detection of atrial fibrillation sometimes after original classification4. Though a significant portion of ESUS patients are found to have atrial fibrillation, it is not often detected on presentation. Additionally, ESUS patients can present with a large‐vessel occlusion (LVO), often with a high initial NIHSS. It may be of benefit to compare ESUS patients with and without LVO on the basis of detection of atrial fibrillation. Methods This study is a retrospective cohort study of patients discharged from the Neurology general practice unit, Stroke step‐down unit, or Neurosurgical ICU from January 2014 to June 2022.Subject charts will be reviewed for the following variables: 1)Demographics: Age, race, sex, 2)Use of antithrombotics, 3)Specific antithrombotics prescribed, 4)Stroke etiology, 5)Initial NIHSS, 6)Presence of large vessel occlusion (LVO), 7)Received tPA, 8)Received MER, 9)Detection of atrial fibrillation, 10)Detection of arrhythmia, 11)Presence of reduced ejection fraction, 12)Received Holter monitor, 13)Underwent internal loop recorder placement, 14)Recurrence of stroke or TIA. Results ESUS patients often present with atrial fibrillation. ESUS patients can present with a large‐vessel occlusion (LVO). There was a higher rate of detection of atrial fibrillation in patients with ESUS who present with LVO in comparison to patients with ESUS who do not present with LVO. Conclusions This study demonstrated that there may be an increased likelihood of atrial fibrillation in patients with ESUS who present with LVO versus those who do not present with LVO. Areas of further development include prevention of LVO‐related ischemic stroke in patients with atrial fibrillation, targeted LVO education for patients with atrial fibrillation, earlier initiation of anticoagulant stroke preventive medication for high‐risk LVO patients. The study may also help elucidate whether extended cardiac monitoring would be beneficial for patients who present with an LVO.